MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN MENGGUNAKAN STRATEGI KNOW WANT TO LEARN (KWL) PADA SISWA KELAS V SD INPRES 15 HALMAHERA BARAT - Meike Awa; Suhardi Abdullah; Kodrat Hi. Karim; Anwar Marasabesy (EDUKASI, 2020)
The research objectives consist of (1) To increase students reading comprehension understanding in using Know Want and To Learn strategy and (2) To Describe the students reading comprehension ability in using this teaching strategy by the students of 5th grade  SD Inpres Halmahera Barat. Classroom action research has become the kind or type of research that used it. Thus the research consists of planning, action, observation, and reflection. Also, this research used quantitative and qualitative approaches in determining the data analysis. The data considered by the testing process, observation activities (between students and teachers), and also students post-test. The result of both cycles was as follows: (1) the student’s reading comprehension ability score averages at the first cycle were 70 and in the second cycle became 95. It means that the learning strategy functions better in the process and also students’ capability in reading comprehension learning objectives is reached.